The Effect Size of Inquiry Based Learning Containing Ethno-Physics on Students 21 Century Thinking Skills - Meriyati; Bucky Wibawa Karya Guna; Muhammad Ichsan Abda; Asmawati; Sutarto; Unpris Yastanti (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The purpose of this study was to determine the effect of ethno-physics-based inquiry-based learning on students' 21st century thinking skills. This type of research is quantitative research with meta-analysis methods. The data comes from an analysis of 14 national and international journals published in the last 5 years 2019-2024. The data search keyword is inquiry based learning model; Inquiry-based learning based on ethno-physics and students' 21st century thinking skills. Search for data sources through google scholar; ERIC and Mendeley. Data analysis in this study is a quantitative analysis by calculating the effect size value of each study with the Microsoft excel 2020 application building. The results of this study concluded that the ethno-physics-based inquiry-based learning model had a significant effect on students' 21st century thinking skills with an average value of effect size ES = 0.837 (high effect size). These findings provide important information that the implementation of ethno-physics-based inquiry-based learning has a positive impact on students' 21st century thinking skills.